Модель влияния физического поля на биологический объект - Гемба, В. Н.; Дацок, О. М.; Мустецов, Н. П. (НТУ "ХПИ", 2006)
Робота присвячена механізмам дії низкоінтенсивних електромагнітних полів на біологічні об‘єкти. Пропонована модель, яка адекватна експериментальним результатам.

The article discusses mechanisms of low energy electromagnetic field influence to biological entity. The considered models are adequate to known experimental results, some original principles are proposed for physiotherapy apparatus building.
Keywords: ЭМПМИ; БО; электромагнитное поле; терапевтический эффект; заболевания